Advanced strategies of Orthosiphon stamineus Benth as antioxidants and α-glucosidase inhibitors using metabolomic and marker-based approaches - Ahda, Mustofa; Ahmed, Qamar Uddin; Jaswir, Irwandi; Mahfudh, Nurkhasanah; Rohman, Abdul; Helal Uddin, A.B.M.; Parveen, Humaira; Mukhtar, Sayeed; Khatib, Alfi (Elsevier, 2026)
Orthosiphon stamineus Benth (O. stamineus) is a widely recognized medicinal plant traditionally used to manage various ailments, notably diabetes. Its therapeutic potential is primarily attributed to key bioactive compounds, namely sinensetin, rosmarinic acid (RA), and 3′-hydroxy-5,6,7,4′-tetramethoxyflavone (TMF) which exhibit potent antioxidant properties and effectively inhibit α-glucosidase enzymes, a mechanism crucial for regulating postprandial blood glucose levels. In the modern era, the identification of chemical compounds in medicinal herbs has been revolutionized by advanced analytical techniques combined with statistical tools, forming what is known as a metabolomic approach. Metabolomics is a powerful analytical approach that investigates the metabolome, the complete set of small-molecule metabolites (typically <1 kDa) involved in biological processes. This technique provides critical insights into biochemical activities and physiological responses. As a member of the omics sciences, metabolomics emerged after genomics, transcriptomics, and proteomics, offering a complementary layer of information that reflects the dynamic state of cellular metabolism. It offers numerous advantages, including enhanced quality control, biomarker identification, and support for therapeutic decisionmaking. In this study, we have employed the metabolomic approach to identify chemical compounds in O. stamineus, with a particular focus on antioxidants and α-glucosidase inhibitors. Current research highlights caffeic acid, rosmarinic acid, and chlorogenic acids as potential quality markers for standardizing O. stamineus extract quality. Furthermore, spectroscopy and chromatography-based metabolomic approaches provide robust platforms for ensuring the consistency, efficacy, and safety of this herbal preparation.